Blueprint for health security in Nigeria by 2050: Ageing and ageing- related diseases (2019)
Background: Nigeria is currently populated by about 200 million people of diverse ethnic, cultural and religious inclinations. Projections estimate that the proportion and absolute number of older persons aged 60 years and above (currently about 5% of the total population) will increase to 25 million by the year 2050. Ageing of the Nigerian population has far reaching multifaceted economic, psychosocial, educational and health implications. Situation analysis: In this paper, a scenario-based analysis is presented on the likely trajectory of health security for older Nigerians by the year 2050. Ageing – associated diseases are predominantly non - communicable (NCD) and their burden is likely to increase over the next 30 years. The combined burden of NCDs and infectious diseases (malaria, tuberculosis, HIV/AIDS, emerging and re – emerging diseases) suggest that the demand on health services (preventive, diagnostic, curative, rehabilitative and palliative care) from older persons and the elderly will increase in tandem with the growth of this segment of the population. Conclusion: A blueprint for achieving healthy ageing for older persons by the year 2050 is presented. This encompasses set targets, strategic plans and a monitoring and evaluation scheme. Improved funding and coverage of the National Health Insurance Scheme, better pensions and retirement benefit coverage, other social schemes and policy interventions and rigorous implementation schemes are all required for achieving health security by the year 2050 with respect to ageing and ageing – related disorders.